Optimalisasi Manajemen Risiko Jatuh pada Pasien Psikiatri melalui Penggunaan Tool Asesmen yang Tepat - Tri Ilmiah Fattah; Rr Tutik Sri Hariyati; Nurdiana Nurdiana; Andi Amalia Wildani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify fall management problems in psychiatric patients, conduct analysis, develop a plan of action, implement psychiatric fall management innovations, and evaluate the use of appropriate assessment tools in the psychiatric population. The method used is a case report using the ADDIE approach. The research results showed that the attitudes and involvement of nurses in fall management were high (99.42% and 98.86%). However, the results of the focus group discussion (FGD) in the psychiatric room found data that the fall risk assessment tool currently used, namely the fall Morse scale (FMS), has not accommodated the condition of psychiatric patients, namely there is no assessment of psycho-pharmaceutical drugs, sedative drugs and activity and patient elimination. Evaluation of the successful implementation of appropriate fall risk assessment tools in the psychiatric population is seen from the nurses' opinions about the ease of use of the tools, the ease of assessing a patient's risk of falling, and the devices that can accommodate the conditions of psychiatric patients. The result is that 62% recommend using the Wilson-Sims Fall Risk Assessment Tool (WSFRAT), and 38% recommend using the Edmonson Psychiatric Fall Risk Assessment Tool (EPFRAT). In conclusion, using appropriate fall risk assessment tools in the psychiatric population can reduce the incidence of falls and make it easier for nurses to assess the risk of falls in psychiatric patients. Keywords: Patient Safety, Risk Management, Psychiatry, Fall Risk Assessment Tool